A simplified table for staging embryos of the pipid frog Pipa arrabali - Araujo, Olivia G. S. [UNESP]; Haddad, Celio F. B. [UNESP]; Silva, Helio R. da; Pugener, Lourdes A. (Acad Brasileira De Ciencias, 2016)
Pipa is a Neotropical genus of frogs that dwell in freshwater environments. It includes four species that lack free-swimming larvae (P. aspera, P. arrabali, P. pipa, and P. snethlageae) and three with tadpoles (P. carvalhoi, P. myersi, and P. parva). Developmental tables such as the one proposed by Nieuwkoop and Faber might be useful for Pipa species with tadpoles. However, for the other Pipa species, to determine stages by this table or by any of the tables already prepared for frogs without tadpoles (e.g., Crinia nimbus, Eleutherodactylus coqui, and Oreobates barituensis) is impossible. By using embryonic, juvenile, and subadult specimens, we generated a staging table for P. arrabali, from the moment limb buds were first observed until birth, based on diagnostic features such as snout-vent length; growth, morphology, and reabsorption of the external tail; growth and differentiation of fore and hind limbs; development of intestine and vent tube; position of the angle of the mouth relative to nostrils and eyes; and color of preserved individuals. Based on these observations, we discuss some noteworthy traits (e.g., posture of hands and feet). We also compare the pattern of development of P. arrabali with that of other anuran species (with and without tadpoles).
Keywords: Amphibia; Anura; development; morphology; Pipidae